Sulphur metabolism and cellulase gene expression are connected processes in the filamentous fungus Hypocrea jecorina (anamorph Trichoderma reesei) - Gremel, Gabriela; Dorrer, Marcel; Schmoll, Monika (BMC microbiology, 2008)
Sulphur compounds like cysteine, methionine and S-adenosylmethionine are essential for the viability of most cells. Thus many organisms have developed a complex regulatory circuit that governs the expression of enzymes involved in sulphur assimilation and metabolism. In the filamentous fungus Hypocrea jecorina (anamorph Trichoderma reesei) little is known about the participants in this circuit. Analyses of proteins binding to the cellulase activating element (CAE) within the promotor of the cellobiohydrolase cbh2 gene led to the identification of a putative E3 ubiquitin ligase protein named LIMPET (LIM1), which is an orthologue of the sulphur regulators SCON-2 of Neurospora crassa and Met30p of Saccharomyces cerevisiae. Transcription of lim1 is specifically up-regulated upon sulphur limitation and responds to cellulase inducing conditions. In addition, light dependent stimulation/shut down of cellulase gene transcription by methionine in the presence of sulphate was observed. Further, lim1 transcriptionally reacts to a switch from constant darkness to constant light and is subject to regulation by the light regulatory protein ENVOY. Thus lim1, despite its function in sulphur metabolite repression, responds both to light as well as sulphur- and carbon source. Upon growth on cellulose, the uptake of sulphate is dependent on the light status and essential for growth in light. Unlike other fungi, growth of H. jecorina is not inhibited by selenate under low sulphur conditions, suggesting altered regulation of sulphur metabolism. Phylogenetic analysis of the five sulphate permeases found in the genome of H. jecorina revealed that the predominantly mycelial sulphate permease is lacking, thus supporting this hypothesis. Our data indicate that the significance of the sulphate/methionine-related signal with respect to cellulase gene expression is dependent on the light status and reaches beyond detection of sulphur availability.